Pengembangan booklet digital berbantuan HTML 5 pada materi keragaman budaya Indonesia siswa kelas XI SMA - Hasna Indriani; Fatiya Rosyida; Djoko Soelistijo; Yusuf Suharto (Universitas Negeri Malang, 2023)
The need for teaching materials in supporting learning that is adapted to student learning conditions is very necessary. Based on the phenomena in the field, it is known that there is a need for teaching materials that can help students understand the material and support online learning. The purpose of this research is to produce a supplement product for teaching materials in the form of digital booklets assisted by HTML 5 technology to support geography learning, especially material on cultural diversity in Indonesia. The research uses the ADD development model which consists of the Analyze, Design and Development stages. The research subjects were material expert validators, teaching materials and linguistics as well as teachers and students of class XII SMA Negeri 5 Malang. The results obtained from the percentage of teaching material validation are 96 percent in the